The Student Management Based on Participants in Improving Quality of Tahfidz Program with Supply Chain Practices - Ahmad Tanzeh; Sofingatun Sofingatun; Achmad Patoni; Mukhamad Sukur; Abd. Aziz (International Journal of Supply Chain Management, 2020)
Abstract- Many global supply chains are unequipped to cope with the world we are entering. For that reason, supply chain managers need to shift their attention from cu tting costs to enabling new processes, and make corporations more connected and agile to create value across the enterprise. Student management is very important in improving the quality of education programs in Islamic boarding schools, especially in memorizing Alquran (tahfidz) programs. Tahfidz program provides learning for the students to be disciplined, independent, and good attitude. Islamic boarding schools are one of the educational institutions that conduct non-formal education in the field of Islamic materials. In transferring the knowledge from the teacher to students, Islamic boarding schools have two programs, namely the madrasah diniyyah program for, learning books. Secondly, the Alquran education program (TPQ) for learning the correct and fluent in the reading of the Alquran. Moreover, today there are a lot of Islamic boarding schools that run memorization programs of the Qur'an (Tahfidzul Quran). In order to succeed in the tahfidzul Quran program in Islamic boarding schools, resources that are needed to carry out management activities such as supply chain management. In this case, to support the implementation of the Tahfidzul Qur'an program based on its purpose, a management activity is needed. The management in question is how the institution plans, implements, and conducts evaluation activities. One management that can support the achievement of the objectives of the institution here is the management of students.